Impact of Local employee Guanxi on Job Satisfaction and TurnoverIntention: the Mediating Role of Job Security - Alwaheeb, Mohammed Abdulwahab; Jianqiao, Liao (European Scientific Journal, ESJ, 2016)
In the recent past, Saudi Arabia has experienced an influx of foreign workers. Most of the jobs that were traditionally occupied by the locals are now taken up by foreign workers. We explore the Guanxi and country policies that have dictated the job situation in this particular region. (Cooper, 2006) In this article we look into the both literature review and research methodologies used in the study. The exchange favors and the relationships created with business mindset are as well suggested. Additionally this article elaborates on the research type of research used in establishing the predetermined objectives. Data sampling methods and their significance are considered. It gives a reflection on the real Guanxi policies on the job market currently (Eisenberger, 2001). The article investigates the policies implemented to curb conflict development between locals and foreigners. The implications of the Guanxi policies are implemented. Given that the locals are now skilled to occupy the jobs but are still missing the opportunities.